Die humanistiese mensbeeld - Labuschagne, J. P. (Hervormde teologiese studies, 1991)
The humanistic understanding of man The main purpose of this essay is to reflect on the humanistic understanding of man, and on the influence it has on the church. For the humanist man’s understanding of himself actually determines his own being. On the other hand, what man experiences of his own being and the world he has created for himself occupies his mind, and this again determines his thoughts.